Gender and Religious Leadership: Women Rabbis, Pastors, and Ministers - Bomhoff, Hartmut; Eger, Denise L.; Ehrensperger, Kathy; Homolka, Walter (Lexington Books, 2019)
This volume analyzes historical and recent developments in female religious leadership and the larger issues shaping the scholarly debate at the intersection of gender and religious studies. Jewish activism and scholarship have been crucial in linking theology and gender issues since the early twentieth century. Academic and vocational leadership and training have had significant, concrete impact on religious communal practices and formation across the US and Europe. At the same time, these models provide important avenues of constructive dialogue and comparative ecumenical and interfaith enterprises. This volume investigates those possibilities towards constructive, activist, holistic female ministerial leadership for religious faith communities.